A Novel Class of Small Molecule Inhibitors of Hsp90 - Yi, Fang (2008)
Unregulated cellular proliferation, caused by mutation or dysregulation of growth-promoting proteins, is an underlying cause of cancer. Many such growth-promoting proteins exhibit an increased dependence on the activity of the chaperone heat-shock protein 90 (Hsp90) for correct folding and maturation in the cell. One can therefore envision that inhibition of Hsp90 would be an effective and broadly applicable strategy for the development of anticancer agents. Hsp90 functions in multichaperone complexes driven by the binding and hydrolysis of ATP. Encouraging results have been obtained by inhibiting Hsp90 with 17-AAG, an active-site binding ATP analog. Here we present the results of a different approach to inhibiting Hsp90 by disrupting its interaction with a cochaperone named Hsp organizing protein (HOP). We have used an AlphaScreen technology based high-throughput in vitro screen to identify compounds that inhibit this interaction. In addition, we demonstrate that these compounds are active in vivo. Treatment of human breast cancer cell lines BT474 and SKBR3 with these compounds decreases the levels of the Hsp90-dependent client protein HER2, with associated cell death.